The Universal Enveloping Algebra of the Schrödinger Algebra and its Prime Spectrum. Issue 4 (1st December 2018) - Bavula, V. V.; Lu, T.
Abstract: The prime, completely prime, maximal, and primitive spectra are classified for the universal enveloping algebra of the Schrödinger algebra. The explicit generators are given for all of these ideals. A counterexample is constructed to the conjecture of Cheng and Zhang about nonexistence of simple singular Whittaker modules for the Schrödinger algebra (and all such modules are classified). It is proved that the conjecture holds 'generically'.